Sifat Fisik, Kimia, dan Sensori Mi Instant yang Terbuat dari Tepung Komposit Terigu dan Pati Kimpul Modifikasi - I Nengah Kencana Putra; I Putu Suparthana; Anak Agung Istri Sri Wiadnyani (Faculty of Animal and Agricultural Sciences, Diponegoro University, 2019)
Pati kimpul modifikasi (PKM) merupakan pati yang dibuat dari umbi kimpul yang diberikan perlakuan fisik atau kimia sehingga mempunyai sifat fungsional lebih baik dibandingkan dengan pati kimpul alami. Pada penelitian ini, dievaluasi pengaruh komposisi tepung komposit (terigu-PKM) terhadap sifat fisik, kimia, dan sensori mi instant. PKM dibuat menggunakan metode high moisture treatment (HMT), yaitu pemanasan pati pada suhu 110˚C pada kadar air 30% selama 10 jam. Tepung komposit dibuat dengan menggunakan berbagai perbandingan terigu dan PKM (90:10, 80:20, 70:30, 60:40, 50, dan 50). Selanjutnya, tepung komposit ini diolah menjadi mi instan, dan kemudian sifat fisik, kimia, dan sensori mi instan yang dihasilkan dievaluasi. Hasil penelitian menunjukkan perbandingan terigu dan PKM pada tepung komposit berpengaruh nyata terhadap kadar air, kadar protein, kadar karbohidrat, waktu pemasakan, kehilangan padatan akibat pemasakan (KPAP), dan daya serap air mi instan. Berdasarkan hasil uji sensori, tepung komposit terigu-PKM (80:20) menghasilkan mi instan terbaik. Komposisi zat gizi mi instan yang dihasilkan adalah: kadar air (2,74%), lemak (29,19%), protein (7,68%), dan karbohidrat (58,91%). Mi instan terigu-PKM (80:20) memiliki aroma lebih baik, waktu pemasakan lebih singkat, dan daya serap air lebih baik dibandingkan mi terigu 100%, namum memiliki KPAP lebih tinggi. Kesimpulannya, PKM dapat digunakan sebagai pensubstitusi sebagian terigu dalam pembuatan mi instant.Physical, Chemical, and Sensory Properties of Instant Noodles Prepared from Wheat - Modified Tannia Starch CompositeAbstractModified tannia starch (MTS) is the starch made from tannia tuber, which is provided a physical or chemical treatment so that it has better functional properties compared to native tannia starch. In this study, the effect of the composition of the wheat flour-MTS composite on the physical, chemical, and sensory properties of instant noodles was evaluated. MTS was produced by using the high moisture treatment (HMT) method, which was heating the starch at the temperature of 110˚C and moisture content of 30% for 10 hours. The composite flour was made with various ratios of wheat flour and MTS (90:10, 80:20, 70:30, 60:40, 50, and 50). Subsequently, the composite flour was processed into instant noodles, and then the physical, chemical, and sensory properties of the noodles produced were evaluated. The results showed the ratio of wheat flour and MTS had a significant effect on the water content, protein content, carbohydrate content, cooking time, cooking loss, and water absorption capacity of the instant noodle. Based on the results of sensory evaluation, the composite of wheat flour-MTS (80:20) could produce the best instant noodles. The nutrition composition of the instant noodles produced, namely: water content (2.74%), fat content (29.19%), protein content (7.68%), and carbohydrate content (58.91%). If compared to the 100% wheat flour instant noodles, the wheat flour-MTS (80:20) instant noodles has a better aroma, better water absorption capacity, and shorter cooking time, but it has a higher cooking loss. In conclusion, MTS can be used as a partial substitute for flour in making instant noodles.